2022
DOI: 10.1002/fsn3.2797
|View full text |Cite
|
Sign up to set email alerts
|

Traditional uses, pharmacological activities, and phytochemical constituents of the genus Syzygium: A review

Abstract: This comprises medicinal plants not only important for the treatment of diseases but also as potential material for maintaining good health and conditions. Better cultural acceptability, better compatibility and adaptability with the human body, and lesser side effects of plants made many countries in the world to depend on herbal medicine for their primary health care (Bari et al., 2021;CHOWDHURY et al., 2021;Hoque et al., 2021). For centuries, plants are being widely used for their natural resources isolated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(37 citation statements)
references
References 233 publications
1
34
0
2
Order By: Relevance
“…Moreover, the downregulation of the expression and activity of antioxidant enzymes such as dehydrogenase complexes is evident in AD, causing biomolecular damage (lipids, proteins, and DNA) and neuronal death [ 4 ]. Antioxidants help scavenge free radicals and balance the production of RIS to reduce oxidative damage [ 84 ].…”
Section: Neuroprotective Agents From Syzygiummentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the downregulation of the expression and activity of antioxidant enzymes such as dehydrogenase complexes is evident in AD, causing biomolecular damage (lipids, proteins, and DNA) and neuronal death [ 4 ]. Antioxidants help scavenge free radicals and balance the production of RIS to reduce oxidative damage [ 84 ].…”
Section: Neuroprotective Agents From Syzygiummentioning
confidence: 99%
“…Syzygium is undeniably a great source of antioxidant agents due to the presence of polyphenols, tannins, and flavonoids [ 84 ]. The evidence of antioxidant activities from Syzygium species was summed up in Table 3 .…”
Section: Neuroprotective Agents From Syzygiummentioning
confidence: 99%
“…They are widely distributed in the tropical and sub-tropical regions of Africa, Madagascar, Asia, and throughout Oceania and the Pacific, with the highest diversity found in Australia and Southeast Asia (Craven and Biffin, 2010;Nigam et al, 2012;Tuiwawa et al, 2013). Some Syzygium species have been used as a traditional medicine to treat diabetes, opium poisoning, liver disorders, centipede bites, renal problems, dysentery, inflammation, leucorrhoea, stomachache, fever, constipation, vomiting, dermopathy, bleeding disorders, and metrorrhagia (Cock and Cheesman, 2018;Uddin et al, 2022;Kadir et al, 2022). Previous phytochemical studies on Syzygium species have revealed the presence of secondary metabolites such as terpenoids, lignans, chalcones, flavonoids, tannins, alkyl phloroglucinols, and chromone derivatives (Aung et al, 2020;Uddin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Some Syzygium species have been used as a traditional medicine to treat diabetes, opium poisoning, liver disorders, centipede bites, renal problems, dysentery, inflammation, leucorrhoea, stomachache, fever, constipation, vomiting, dermopathy, bleeding disorders, and metrorrhagia (Cock and Cheesman, 2018;Uddin et al, 2022;Kadir et al, 2022). Previous phytochemical studies on Syzygium species have revealed the presence of secondary metabolites such as terpenoids, lignans, chalcones, flavonoids, tannins, alkyl phloroglucinols, and chromone derivatives (Aung et al, 2020;Uddin et al, 2022). Modern pharmacological studies have shown the bioactivities of these metabolites, such as antioxidant, antibacterial, anticancer, anti-inflammatory, hepatoprotective, and antidiarrheal activities (Aung et al, 2020;Uddin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation